Inovasi Teknologi Tepat Guna Lampu Sensor Otomatis dengan Kotak Saran Digital di Desa Pandanarum - Noval Erick Ramadhani; Tyo Surya Agung; Nazhari Dhiyaul Hilmi; Stefani Beatrix; Milla Dwi Cahyani; Thesna Widya Fandhyta; Rizkya Dwijayanti; Dia Puspitasari (Journal of Community Service and Engagement, 2026)
This community service program aimed to implement appropriate technology through automatic sensor-based street lighting and a digital suggestion box in Pandanarum Village. The initiative addressed two main local issues, namely insufficient street lighting in village alleys and limited access to safe and practical channels for citizens to express aspirations. The method employed direct field observation, participatory planning with village officials, technology installation, community assistance, and evaluation using interviews and questionnaires. The results indicate that the automatic sensor lights improved environmental lighting quality, energy efficiency, and residents’ perceived sense of security during nighttime activities. At the same time, the digital suggestion box, accessed through barcode-linked anonymous forms, increased community participation in conveying feedback related to public services and village facilities. Evaluation data demonstrate that the technologies functioned reliably and were well received by both residents and village administrators. This program confirms that simple, user-friendly technologies aligned with community needs can effectively enhance village safety, social participation, and governance responsiveness, while offering strong potential for replication and further development in similar rural contexts..